Optimization of Microgel Formula Combination of Snail Mucus and Catechin to Accelerate Wound Closure - Azizah, Adinda Fayi; Astuti, Ika Yuni; Syarifah, Arini; Kumalasari, Raudia; Agistya, Lusyahaura; Talitarahma, Anindya Tian (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Incised wound healing is a crucial process that requires effective treatment solutions. A microgel containing snail mucus and catechin seems a promising approach to accelerate healing and improve recovery outcomes. This study aimed to develop a microgel preparation contain snail mucus (Achatina fulica) and catechin. Formulation design is assisted using the Design Expert SLD method. The optimum formula was achieved with a carbopol to TEA ratio of 1.589:0.411, with estimated values of pH (4.506), viscosity (18,873 cPs), spread ability (5.477 cm), and adhesion (2.068 second). These estimated values showed no significant difference from the actual values obtained in the laboratory experiments. To evaluate the quality of the preparation, in vivo testing was performed on white mice, and the data were analysed using one-way ANOVA. The snail mucus and catechin microgels were proven to be effective in treating deep incision wounds.